INNOVATIVE DIGITAL TECHNOLOGIES FOR ORGANIZING AND PROMOTING EVENTS AS PART OF EFFORTS TO IMPROVE THE OPERATIONAL EFFICIENCY OF HOTEL BUSINESSES - Radionova , O. M.; Vlashchenko , N. M. (Systems and Technologies, 2026)
This article examines the role of innovative digital technologies in organizing and promoting events as part of efforts to improve the operational efficiency of hotel businesses. It demonstrates the relevance of implementing digital solutions in the context of growing competition in the hotel services market and the need to optimize business processes. It is determined that the digitalization of event activities serves as a key factor in transforming approaches to event management, customer interaction, and the creation of added value in hotel services. Within the scope of the study, innovative digital technologies were categorized according to the stages of event organization, and their essential characteristics and functional capabilities were summarized. It has been established that the use of event management systems, CRM solutions, mobile applications, analytical platforms, artificial intelligence tools, and automated services ensures increased efficiency in managing event processes, optimization of resource costs, and improved quality of customer service. It is proved that the systemic integration of CRM and PMS ensures significant automation of routine operations, which directly affects the reduction of operating costs and the growth of ADR and RevPAR indicators. Innovative digital technologies for promoting events were examined, including tools for targeted advertising, social media, email marketing, SEO optimization, and marketing analytics. Their role in shaping demand, expanding the customer base, and increasing the visibility of hotel enterprises has been substantiated. It has been determined that the integration of digital tools into the processes of organizing and promoting events has a comprehensive impact on the operational, marketing, and communication effectiveness of hotel operations. The impact of events on key performance indicators of hotel enterprises has been established, specifically room occupancy rates, ADR and RevPAR metrics, revenue from ancillary services, and customer loyalty levels. The use of cloud solutions (SaaS) as a tool to minimize risks associated with the shortage of digital competencies among staff is justified. A model of the impact of innovative digital technologies for organizing and promoting events on the performance of hotel enterprises is proposed, reflecting the interrelationship between resources, digital tools, processes, and results. The results obtained contribute to deepening theoretical approaches to the study of the digitalization of event activities in the hotel industry and expand understanding of the role of innovative digital technologies in improving the operational efficiency of hotel enterprises in the context of the modern market environment.